2002
DOI: 10.1086/339012
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine Enhances Human Immunodeficiency Virus Replication in a Model of Severe Combined Immunodeficient Mice Implanted with Human Peripheral Blood Leukocytes

Abstract: Epidemiologic studies have identified cocaine as a cofactor for development of acquired immunodeficiency syndrome (AIDS). To evaluate this interaction, human peripheral blood leukocytes (PBL) were implanted into severe combined immunodeficient mice and infected with human immunodeficiency virus (HIV) in both the presence and absence of cocaine. Concurrent administration of cocaine resulted in significantly more PBL becoming infected with HIV in vivo (38.85% vs. 18.5%). The number of CD4(+) cells recovered from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
79
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(86 citation statements)
references
References 14 publications
6
79
0
1
Order By: Relevance
“…For example, in vitro experiments suggest that HIV replication is maximally stimulated by 24 hours of exposure to nanomolar cocaine concentrations and normalizes to control levels at higher concentrations (Peterson et al, 1991;Peterson et al, 1992). A similar increased HIV replication, as well as altered immune cell populations in peripheral tissues, was reported following a 5 mg/kg dose of cocaine in SCID mice (Roth et al, 2002;Roth et al, 2005). Although these reports suggest that cocaine doses lower than the 20 mg/kg dose used in the present experiment might enhance HIVE parameters, whether these lower doses are relevant to the drug's rewarding/reinforcing effects in SCID mice is unknown.…”
Section: Discussionsupporting
confidence: 79%
“…For example, in vitro experiments suggest that HIV replication is maximally stimulated by 24 hours of exposure to nanomolar cocaine concentrations and normalizes to control levels at higher concentrations (Peterson et al, 1991;Peterson et al, 1992). A similar increased HIV replication, as well as altered immune cell populations in peripheral tissues, was reported following a 5 mg/kg dose of cocaine in SCID mice (Roth et al, 2002;Roth et al, 2005). Although these reports suggest that cocaine doses lower than the 20 mg/kg dose used in the present experiment might enhance HIVE parameters, whether these lower doses are relevant to the drug's rewarding/reinforcing effects in SCID mice is unknown.…”
Section: Discussionsupporting
confidence: 79%
“…Methamphetamine itself also increased replication of feline immunodeficiency virus in cultured feline astrocytes (29). Likewise, cocaine, which was abused occasionally by the majority of the HIV-positive subjects with a history of chronic methamphetamine use in the current study, might further enhance HIV replication (30), although cocaine's direct effect on N-acetylaspartate would be minimal (31). Thus, the intermittently increased viral burden in the combined condition might exacerbate brain injury.…”
Section: Discussionmentioning
confidence: 73%
“…Cocaine increases HIV infection of human PBMCs in vitro (12,177). Roth et al, using a model of human PBMCs implanted into severe combined immunodeficient (SCID) mice, demonstrated that cocaine treatments resulted in increased numbers of HIV-infected PBMCs and viral load, as well as a decreased CD4/ CD8 ratio (192). These immunomodulations may be through receptors located in the periphery, as was demonstrated with cocaine-induced suppression of mitogen-stimulated lymphoproliferation (171).…”
Section: Cocaine and Infectionsmentioning
confidence: 99%